Dysregulated vitamin D signaling in Hashimoto’s thyroiditis: an integrated transcriptomic study in a Korean cohort - Lim, Dong-Woo; Jeong, Ho-Jung; Lee, Jin Seok; Choi, Min-Seo; Fang, Sungsoon; Wang, Jing-Hua; Kim, Hojun; Kim, Seok-Mo (Frontiers in Endocrinology, 2025)
BackgroundHashimoto’s thyroiditis (HT) is the most common thyroid disease leading to hypothyroidism in developed countries. Recent studies have highlighted vitamin D as a potential risk factor or therapeutic agent for HT owing to its role in modulating immune responses, although concrete evidence has not been presented. This retrospective observational study was conducted to investigate serum vitamin D levels and dysregulation of vitamin D signaling pathways in patients with HT.MethodsPatients who underwent thyroid surgery for various thyroid neoplasm with or without HT were recruited. We analyzed serum thyroid biomarkers, including serum vitamin D, anti-thyroglobulin (TG) antibody, and anti-thyroid peroxidase (TPO) antibody for patients with HT. Using RNA-seq, the gene expression profile of thyroid tissue and the potential correlation between HT and vitamin D levels or its signaling were investigated.ResultsThe serum vitamin D levels were significantly lower in patients with HT. However, vitamin D receptor (VDR) expression and genes involved in vitamin D-associated biological process (BP) were significantly upregulated in the HT group. Visualization of expression profile on Wikipathways revealed multifaceted regulation of vitamin D-related pathways in the HT group. Real-time PCR and immunofluorescence staining confirmed enhanced VDR expression in thyroid tissues from the HT cohort.ConclusionOur study presents RNA-seq data acquired from the Korean HT cohort in this study, and highlighted dysregulated vitamin D signaling in thyroid tissues from the HT cohort. Further investigations are needed to elucidate the causal role of vitamin D signaling in the pathogenesis of HT.